All-Fiber Dual-Wavelength Q-Switched And Mode-Locked EDFL By SMF-THDF-SMF Structure As A Saturable Absorber - Abdul Latiff, Anas; Kadir, N.A; Ismail, E.I.; Shamsuddin, H.; Ahmad, H.; Harun, S.W. (Elsevier, 2017)
-